Measuring the real impact of accredited offending behaviour programmes - Friendship, Caroline (Legal and criminological psychology, 2003)
Purpose. This paper describes an integrated model for the evaluation of offending behaviour programmes in order to assess their real impact. Arguments. To date there has been an over-reliance on reconviction data as the sole measure of treatment efficacy. Reconviction has a fundamental role to play but cannot be considered in isolation from other empirically related treatment and re-settlement factors. A rigorous reconviction study requires an adequate comparison group but few papers describe with transparency how this has been achieved. There is also the assumption that participation in treatment renders an individual offender as treated. A treated profile is contingent upon the treatment climate, the quality of programme delivery and how the individual responds to treatment. The influence of life-style or dynamic risk factors must also be acknowledged in terms of their effect on reconviction. Conclusions. It is recommended that researchers use an integrated approach to the evaluation of accredited offending behaviour programmes. In order to establish a broad balance of treatment outcomes, a shift away from reconviction rates is needed. This paper presents an integrated model for the evaluation of offending behaviour programmes.